Analisis Trend Issu Perkembangan Dunia Teknologi Informasi Untuk Keperawatan atau Kesehatan. - Hendra Veri Setiawan; Lestari, Ida Sri; Je Vidya Putri Wibowo; Ladya Khafidhotun Nazma; Wendy Listyanto (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2022)
Application Of Information And Communication Technology System (ICT) In Health Promotion. The era of globalization is now progressing very rapidly. One of the advances in information tech-nology penetrated the health field. Use and utilization of this technology is one of the right solutions for problem solving public services. At least utilization of it will address the geographical, time and socioeco-nomic issues. Some research mentioned that the utilization of technology in the field of health can improve health service and can change health behavior. Information is a very important thing, because all things related to public health is information that is well managed and safe, so it takes a safe and smooth system for all information obtained can be used for the benefit of health services more optimal and can benefit the entire community.